2022
DOI: 10.1021/acsami.2c09828
|View full text |Cite
|
Sign up to set email alerts
|

Negative Longitudinal Piezoelectricity Coexisting with both Negative and Positive Transverse Piezoelectricity in a Hybrid Formate Perovskite

Abstract: Negative longitudinal piezoelectric response is a rare property, which has been found mostly in inorganic materials. We use first-principles density functional theory simulations to predict such an unusual response in [NH2NH3]­Co­(HCOO)3 a representative of a large family of hybrid organic–inorganic formate perovskites. A feature that sets aside [NH2NH3]­Co­(HCOO)3 from inorganic compounds with a negative longitudinal piezoelectric response is that this rare property coexists with both negative and positive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The data predict a rather smooth dependence of the polarization on uniaxial stress. Interestingly, we find a positive slope for the P x component of polarization and a negative slope for the P z component of polarization, which previously has been reported for formate perovskite . Note that our Cartesian x and y axes are aligned along the a and b crystallographic directions.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The data predict a rather smooth dependence of the polarization on uniaxial stress. Interestingly, we find a positive slope for the P x component of polarization and a negative slope for the P z component of polarization, which previously has been reported for formate perovskite . Note that our Cartesian x and y axes are aligned along the a and b crystallographic directions.…”
mentioning
confidence: 90%
“…Some examples are given in Table . Interestingly, TMCM-CdCl 3 and MPSnBr 3 are already predicted to exhibit PST valence band (VB) and conduction band (CB), respectively. , Hybrid organic–inorganic perovskites are known for hosting a multitude of properties, such as optical, ferroelectric, and magnetic properties, and thus are used in photodetectors, photovoltaics, and actuators, among others. ,, They are relatively soft and flexible and may exhibit high anisotropy of their elastic properties, which in turn could open a way to the tunability of their electronic properties through mechanical deformations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Ghosh et al reported a hybrid organic-inorganic formate perovskite [NH 2 NH 3 ]Co(HCOO) 3 with both positive and negative transverse piezoelectric responses. 16 Zhang et al found that a bismuth-based organic-inorganic hybrid crystal [C 6 H 5 CH(CH 3 )NH 3 ] 4 Bi 2 Br 10 has a large shear piezoelectric coefficient of 46.54 pC N −1 with an electromechanical coupling coefficient over 40%. 17 The development of minimized medical implants and wearable devices requires thin, soft, light weight and flexible piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain the electronic contribution, all ions should be clamped to their own fractional coordinates when applying strains. When applying strain (or stress) to the system, the dipole moment and the area of the system will both change, but the piezoelectricity caused by the change of the area of the unit cell is trivial and useless for applications which should be excluded. , To analyze it, for FeB 2 monolayer considered in this study, the out-of-plane polarization P z determined from eq can be further decomposed with a parallel-plate-capacitor-like model into P z = Q h S where Q is the transfer charge, h is the vertical distance between Fe-layer and B-layer, and S is the area of unit cell. Q can be calculated from P z , z , and S by eq where P z is determined by eq .…”
mentioning
confidence: 99%